Prevalence of maternal mental illness among children and adolescents in the UK between 2005 and 2017: a national retrospective cohort analysis. (June 2019) - Abel, Kathryn M; Hope, Holly; Swift, Eleanor; Parisi, Rosa; Ashcroft, Darren M; Kosidou, Kyriaki; Osam, Cemre Su; Dalman, Christina; Pierce, Matthias
Summary: Background: Little information exists about the prevalence of children exposed to maternal mental illness. We aimed to estimate the prevalence of children and adolescents exposed to maternal mental illness in the UK between 2005 and 2017 using primary care data. Methods: In this national retrospective cohort study, we included children aged 0–16 years born between Jan 1, 1991, and Dec 31, 2015, who were linked to their mothers and registered on the primary care Clinical Practice Research Datalink (CPRD) between 2005 and 2017. We extracted data on diagnosis, symptoms, and therapy from the CRPD to define the following maternal mental illnesses: depression, anxiety, non-affective psychosis, affective psychosis, eating disorders, personality disorders, alcohol misuse disorder, and substance misuse disorder. We also extracted data on socioeconomic status from the Index of Multiple Deprivation 2010 and data on ethnicity from the Hospital Episode Statistics dataset. The main outcome was prevalence of maternal mental illness. Prevalence was calculated for each 2-year period of childhood (from age 0–<2 to 14–<16 years) using marginal predictions from a logistic regression model. We used survival analysis to estimate the incidence and cumulative risk of children experiencing maternal mental illness by age 16 years. Findings: We identified 783 710 children registered in the UK CPRD mother-baby link database, and included 547 747 children (381 685 mothers) in our analysis. Overall prevalence of maternal mental illness was 23·2% (95% CI 23·1–23·4), which increased during childhood (21·9%, 21·7–22·1 among the 0–<2 year age group vs 27·3%, 26·8–27·8 among the 14–<16 year age group). Depression and anxiety were the most prevalent maternal mental illnesses. The proportion of children exposed to maternal mental illness increased from 22·2% (21·9–22·4) between 2005 and 2007 to 25·1% (24·8–25·5) between 2015 and 2017. Geographically, the highest prevalence of maternal mental illness was observed in Northern Ireland (29·8%, 29·0–30·5). In England, prevalence of maternal mental illness was highest among children in the most deprived areas (28·3%, 27·8–28·8). The incidence of maternal mental illness was highest between 0–3 months (26·7 per 100 person years, 26·4–27·1). By age 16 years, the cumulative risk of maternal mental illness was 53·1% (52·8–53·3). Interpretation: One in four children aged 0–16 years are exposed to maternal mental illness and the prevalence of diagnosed and treated maternal mental illness is increasing. Policy makers and commissioners should consider this information and channel resources to target individuals in greatest need. Funding: The European Research Council and the National Institute for Health Research.